Self-Care Strategies for Informal Caregivers of Dependent Older Adults: A Systematic Review (Boletín Semillero de Investigación en Familia, 2025)
Introduction: An informal caregiver is a person who provides non-professional care and may or may not be a relative of the patient. They may experience physical, emotional, and social changes that affect their well-being when they decide to focus more on caring for the patient than on their own needs, which has an impact on their self-care. Objective: To determine the self-care strategies that informal caregivers apply to dependent older adults. Materials and methods: We conducted a qualitative, descriptive systematic review following five stages: problem identification, information retrieval, data selection, data analysis, and reporting. Results: Fifty-seven studies published within the past 10 years were included based on predefined criteria (database, language, country of origin, methodological design, and time frame). Using qualitative coding, we classified self-care strategies into categories and subcategories informed by Dorothea Orem’s Self-Care Deficit Theory (self-care requirements and actions). Conclusions: Mapping self-care strategies among informal caregivers is critical for improving caregivers’ quality of life, informing health-care support, and promoting recovery of physical, mental, and social well-being.
Keywords: Strategies; Self-care; Caregiver; Elderly person; Nursing theory